Poor Sleep Quality Increases Prevalence of Primary Dysmenorrhea on Medical Students - Melinda Didi Yudhanti; . Balgis; . Widardo (Nexus Kedokteran Komunitas, 2014)
Backgrounds: Most of Medical Students have a poor sleep quality due to their academic tasks during their study. This poor sleep quality has a role in the pathogenesis of pain, including primary dysmenorrhea. This study aims to know the relationship between sleep quality and the prevalence of primary dysmenorrhea on Medical Students of Sebelas Maret University. Methods: This study was an analytical observational research with a cross sectional approach. Subjects were selected by purposive sampling and obtained 88 Medical Students of Sebelas Maret University as a sample. Each respondent filled in: (1) Informed consent and biodata form; (2) Questionnaire about dysmenorrhea and its degree; (3) Menstrual Symptom Questionnaire (MSQ); and (4) Pittsburgh Sleep Quality Index (PSQI). The collected data were analyzed using the Fishers Exact Test and then processed with prevalence ratio calculation to determine the relationship between sleep quality and prevalence of primary dysmenorrhea. To know the relationship between sleep quality and the degree of primary dysmenorrhea, the data were then analyzed using Kolmogorov-Smirnov test. Results: Among the 88 students, 76% had poor sleep quality, 77 % had primary dysmenorrhea with 52.3 % mild, 23.9 % moderate, and 1.1 % severe degree. Using Fishers Exact Test, the study found a significant relationship between sleep quality and prevalence of primary dysmenorrhea with (p) = 0.001. Based on the calculation, the prevalence ratio was 2.35 with Confidence of Interval 1.35 4.08. Using Kolmogorov Smirnov Test, there was significant relationship between sleep quality and the degree of primary dysmenorrhea, with the value of (p) = 0.001. Conclusions: Statistically, there is a significant relationship between sleep quality and primary dysmenorrhea problem including its prevalence and degree in the medical Students of Sebelas Maret University Surakarta. Students with poor sleep quality had a risk of 2.35 times more to had primary dysmenorrhea than the ones with good sleep quality. Keywords: primary dysmenorrhea, sleep quality, medical student